Nitrogen chlorosis in unicellular cyanobacteria – a developmental program for surviving nitrogen deprivation. (21st November 2018) - Forchhammer, Karl; Schwarz, Rakefet
Summary: Cyanobacteria evolved sophisticated mechanisms allowing them to cope with environmental depletion of combined nitrogen. Here, we describe progress in understanding the processes involved in acclimation of nondiazotrophic cyanobacteria to nitrogen shortage, known as nitrogen chlorosis. The process includes immediate metabolic changes and degradation of light harvesting complexes as well as long‐term acclimation responses. Consequently, quiescent cells substantially differing from vegetative cells are obtained. Thus, the process leading to these considerable metabolic and morphological changes is referred to as a developmental program. Current understanding of the relevant regulatory processes depicts an intricate mechanism involving modulation of transcription activators by proteinaceous interacting components, as well as by small metabolites reporting the energy status and carbon–nitrogen balance of the cell. In addition, we describe in detail the quiescent state characterizing cells under prolonged starvation and the process of recovery from this dormant chlorotic state. Accumulated data provide an in depth understanding of the mechanisms accompanying the cycling of cyanobacterial cells between vegetative growth, the quiescent‐state and the recovery program, allowing them to regain proliferative growth upon nutrient replenishment.